Entre o Bem e o Mal: Uma abordagem teológico-literária da ambivalência da natureza humana em Incidente em Antares, de Erico Verissimo - Luckner, Rita de Cassia Scocca (2017)
The purpose of this work is a theological-literary approach of the novel Incidente em Antares, written in 1971, by Erico Verissimo (1905 -1975). It is an analysis of the mentioned book, whose aim is to observe the characteristics and attitudes of the characters elaborated by the author and his comic and ironic language as well, used for him in order to deal with matters related to the daily life, and suggests the coexistence of the good and evil which are revealed in human actions. In this way, will be highlighted the situations which were narrated in the book and can be related to some behaviors which refer to the flaws. Therefore, they can be associated to the seven capital sins, listed by Tomas de Aquino and the virtues which oppose them. Accordingly, we will be emphasize the work’s symbolical composition, as well as will be verified the dialogical relation between theology and literature. The components, the sins and virtues, whose are implicitly interconnected, are an introductory element for a reflection about the human nature ambivalence, whereby the correspondence to the seven dead characters from the novel with the known seven capital sins, as well as the actions of the characters that can be related to the virtues, allows through the literary verb to point the human being vocation to the good and to the evil, whose the frontiers is where the hope emerges.